Surfing Online Safety: Assertiveness and Parental Involvement in Adolescents’ Attitudes Toward Cyber Grooming - Hanifah, Raidah; Wigati, Meilia (Bulletin of Counseling and Psychotherapy, 2025)
The development of digital technology presents serious challenges for adolescents, one of which is cyber grooming. Cyber grooming refers to manipulative attempts by perpetrators on social media to exploit victims emotionally or sexually. This study aims to examine the role of assertiveness and parental involvement in shaping adolescents’ attitudes toward cyber grooming. A quantitative approach was employed with a sample of 394 female adolescents aged 13–18 years who accessed social media for at least five hours per day. Multiple linear regression analysis revealed that assertiveness and parental involvement had a highly significant role in adolescents’ attitudes toward cyber grooming. The regression model accounted for 55.1% of the variance in attitudes toward cyber grooming. These findings highlight that the combination of individual skills (assertiveness) and family factors (parental involvement) serves as a key protective factor in fostering adolescents’ resilience against the risk of online exploitation.